Highly efficient removal of patulin using immobilized enzymes of Pseudomonas aeruginosa TF-06 entrapped in calcium alginate beads. (30th May 2022) - Xing, Mengyang; Chen, Yong; Li, Boqiang; Tian, Shiping
Highlights: A patulin degradation strain Pseudomonas aeruginosa TF-06 was isolated. TF-06 degrades patulin into E/Z-ascladiol through intracellular enzymes. Immobilization of intracellular enzymes effectively reduces patulin in apple juice. Abstract: Patulin is a toxic secondary metabolite produced by several moulds, which contaminates fruits and their products posing serious threats to human health. Though several microorganisms and enzymes have been reported to effectively degrade patulin, separation of them from fruit juice challenges the commercial applications. Here, a Pseudomonas aeruginosa strain TF-06 was isolated, its patulin degradation mechanism and optimum conditions for enzyme immobilization were investigated. The results indicated that TF-06 could degrade patulin into non-cytotoxic E/Z-ascladiol mainly by the activity of intracellular enzymes. For easy separation of enzymes, calcium alginate was selected for immobilization of intracellular enzymes from TF-06. The immobilized enzyme beads were effective in detoxification of patulin in apple juice. The mitigation rate was reached 95%, while there was no negative effect on juice quality. The study provides a promising way to resolve the issue of enzyme separation during mycotoxin biological detoxification in fruit juice.